A new method for spectrum monitoring networks design (2013)
In the ITU Spectrum Monitoring handbook, edition 2011, a model for design of radio monitoring systems is suggested. This model is based on the work of Pavliuk et al. In this paper we propose a modified version on the Pavliuk model, using methods from the mobile networks world, like semi-deterministic propagation models and population information. We apply the method for the design of the monitoring network in Costa Rica. © 2013 IEEE.